2020
DOI: 10.1002/ppul.25001
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus seropositivity at birth is associated with adverse neonatal respiratory outcomes

Abstract: Background: More than 60 years since the discovery of the respiratory syncytial virus (RSV), the effects of prenatal exposure to this virus remain largely unknown. In this investigation, we sought to find evidence of RSV seroconversion in cord blood and explore its clinical implications for the newborn. Methods: Offspring from 22 pregnant women with a history of viral respiratory infection during the third trimester of pregnancy (respiratory viral illness [RVI] group) and 40 controls were enrolled in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Interestingly, the serological analysis performed on the mother of the patient showed an elevated titer of antibodies against hRSV, suggesting the possibility of vertical transmission of the virus [40]. Accordingly, a study performed in neonates at birth in which mothers who had a history of respiratory illness during the pregnancy showed anti-hRSV IgA, IgM, and IgG titers in cord blood samples [41]. In these cases, half of the neonates showed respiratory problems that included apnea, respiratory failure, and pneumonia, where 56% of them needed supplemental oxygen [41].…”
Section: Hrsv Infection During Pregnancy and Effects On The Newbornmentioning
confidence: 97%
See 3 more Smart Citations
“…Interestingly, the serological analysis performed on the mother of the patient showed an elevated titer of antibodies against hRSV, suggesting the possibility of vertical transmission of the virus [40]. Accordingly, a study performed in neonates at birth in which mothers who had a history of respiratory illness during the pregnancy showed anti-hRSV IgA, IgM, and IgG titers in cord blood samples [41]. In these cases, half of the neonates showed respiratory problems that included apnea, respiratory failure, and pneumonia, where 56% of them needed supplemental oxygen [41].…”
Section: Hrsv Infection During Pregnancy and Effects On The Newbornmentioning
confidence: 97%
“…Accordingly, a study performed in neonates at birth in which mothers who had a history of respiratory illness during the pregnancy showed anti-hRSV IgA, IgM, and IgG titers in cord blood samples [41]. In these cases, half of the neonates showed respiratory problems that included apnea, respiratory failure, and pneumonia, where 56% of them needed supplemental oxygen [41].…”
Section: Hrsv Infection During Pregnancy and Effects On The Newbornmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown in animal models transplacental transmission of RSV from the lungs of pregnant rats to the developing lungs of their offspring [ 2 ]. More recent studies have confirmed the existence of vertical RSV transmission in humans by: (a) real-time PCR detection of RSV RNA in peripheral blood at birth [ 3 ]; (b) RSV replication in human placenta, where it can be accumulated and then transferred to fetal lung tissues by migrating Hofbauer cells [ 4 ]; and (c) anti-RSV IgA and IgM in the cord blood of newborns delivered from mothers with a history of upper respiratory tract illness in the third trimester [ 5 ]. Also, an independent study confirmed RSV RNA detection in mononuclear cells by droplet digital (dd)PCR in 58% of human cord blood samples tested, with a positivity rate increased up to 80% during winter months [ 6 ].…”
Section: Introductionmentioning
confidence: 99%